2019
DOI: 10.1002/14651858.cd002972.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Formula versus maternal breast milk for feeding preterm or low birth weight infants

Abstract: We thank Kath Wright and Melissa Harden for developing and running the electronic searches and managing the database of study reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 31 publications
0
31
0
3
Order By: Relevance
“…However, the entire range of the microbial groups detected in breast milk are similar with both term and preterm deliveries 61 . Therefore, maternal milk is the preferred mode of feeding for all infants, both term and preterm 51,92‐94 …”
Section: Early Colonization In Healthy Newbornsmentioning
confidence: 99%
“…However, the entire range of the microbial groups detected in breast milk are similar with both term and preterm deliveries 61 . Therefore, maternal milk is the preferred mode of feeding for all infants, both term and preterm 51,92‐94 …”
Section: Early Colonization In Healthy Newbornsmentioning
confidence: 99%
“…Several observational studies have shown that human milk is superior to formula milk in reducing the rate of comorbidities. It is difficult to determine the direct role of human milk in modulating the risk of comorbidities, as randomized controlled trials cannot be conducted due to the ethical implications inherent in the randomization of human milk feeding; thus, observational studies are useful in situations in which randomized controlled trials are unethical [ 4 ]. Despite the potential limitations of observational study designs, several studies have shown that human milk feeding can reduce the rate of bronchopulmonary dysplasia (BPD), sepsis, necrotizing enterocolitis (NEC) and severe retinopathy of prematurity (ROP) more than formula feeding can [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Human Milk and Comorbiditiesmentioning
confidence: 99%
“…Breast milk provides optimal nutrients and protective factors that enhance immune and gastrointestinal systems, as well as supports long-term neurodevelopment of VLBW preterm infants ( Andreas et al, 2015 ; Brown et al, 2019 ; Patra et al, 2017 ; Sammallahti et al, 2017 ; Walker, 2010 ). Current recommendations emphasize that preterm newborn infants should receive the mother's milk or HM donated to the Human Milk Bank (HMB), plus commercial fortifiers to improve the milk composition, since milk is the singular nutritional source for infants ( Bertino et al, 2013 ; Colaizy et al, 2012 ; Dutta et al, 2015 ; Valentine et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%